Spectroscopic characterization of composite lithium materials irradiated with high-temperature plasma. Issue 11 (November 2020) - Budaev, V.P.; Fedorovich, S.D.; Lubenchenko, A.V.; Karpov, A.V.; Belova, N.E.; Gubkin, M.K.
Abstract: High-temperature plasma irradiation of materials leads to significant modification of surface structure, growth of deposited composite films and surface layers with induced self-similar granularity on the scale from macroscales to nanoscale due to strong plasma-surface interaction. The aim of this study was to characterize lithium materials irradiated with high-temperature plasma in the T-10 tokamak and PLM device. The reactivity of lithium leads to reactions with impurities in the plasma and on the vessel. Post-mortem analyses by the X-ray photoemission spectroscopy and X-ray analysis have been used to identify deposits composition and morphology. Lithium carbonate composites have been detected by analysis demonstrating materials mixing and evidence of plasma-induced structure. New structures with the high specific surface area of hierarchical granular are registered. The reference industrial powder of lithium carbonate irradiated with steady-state plasma in the PLM device has acquired a new similar structure demonstrating universal influence of plasma on the structure of irradiated materials. Abstract : Materials science; Plasma physics; X-ray photoemission spectroscopy; Lithium; Lithium carbonate; Plasma test; Plasma induced structure.